On Convergence in L-Valued Fuzzy Topological Spaces. (11th February 2015) - Ramadan, A. A.; El-Dardery, M.; Zhao, Hu
Abstract : We introduce the concept of L -fuzzy neighborhood systems using complete MV -algebras and present important links with the theory of L -fuzzy topological spaces. We investigate the relationships among the degrees of L -fuzzy r -adherent points ( r -convergent, r -cluster, and r -limit, resp.) in an L -fuzzy topological spaces. Also, we investigate the concept of LF -continuous functions and their properties.